2012
DOI: 10.2528/pierc11101409
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetic Field Tunable Yttrium Iron Garnet Millimeter-Wave Dielectric Phase Shifter: Theory and Experiment

Abstract: Abstract-A magnetically tunable passive narrow-band split-mode mm-wave phase shifter based on dielectric resonance in yttrium iron garnet (YIG) is investigated. The novelty here is the demonstration of a phase shifter in the frequency region between two split dielectric resonances in YIG. It is shown that, under certain conditions, the differential phase shift from the split modes add up, resulting in a larger phase shift than for a single mode phase shifter. Two prototype phase shifters operating in the U-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…This study resulted in the lowest insertion loss value of 0.25 dB. The insertion loss value found in this study appears to be superior to those reported in the literature [18][19][20][21][22][23][24][25] . This lower insertion loss value indicates that the ferrite garnet sample obtained has a higher phase purity, meaning that the secondary phase is relatively very low or practically non-existent.…”
Section: Microwave Response Performancecontrasting
confidence: 61%
“…This study resulted in the lowest insertion loss value of 0.25 dB. The insertion loss value found in this study appears to be superior to those reported in the literature [18][19][20][21][22][23][24][25] . This lower insertion loss value indicates that the ferrite garnet sample obtained has a higher phase purity, meaning that the secondary phase is relatively very low or practically non-existent.…”
Section: Microwave Response Performancecontrasting
confidence: 61%
“…A similar approach was used by using other additives such as MgO, CuO, and LiBZn, respectively [8][9][10]. However, the presence of these additives usually results in with the formation of unnecessary secondary phases, such as BiFeO 3 and Bi 2 O 3 . Meanwhile, the issue of long sintering duration was addressed by the utilization of the microwave sintering method [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…These properties are very useful, especially in microwave communication devices such as oscillators and phase shifters [1][2][3]. Many methods have been used to produce YIG, but the most economical, simple and practical method among them is the conventional solid-state reaction (CSSR).…”
Section: Introductionmentioning
confidence: 99%
“…This ferrimagnetic material is used widely in electronic devices for the microwave region [3,4] as well as phase shifters, magneto-optical [2] applications and also in wireless communications, surveillance, sensing and tracking [5,6]. Some magnetic performances such as coercive force and initial permeability, are strongly dependent on the microstructural aspects, i.e.…”
Section: Introductionmentioning
confidence: 99%